Doppler Satellite Positioning of Offshore Structures - Hothem, L. D.; Strange, W. E. (The International Hydrographic Review, 2015)
Both for reasons of accuracy of results and economy of operation, Doppler satellite positioning has become an important technique for extending geodetic control surveys into the offshore areas. Fixed-site Doppler satellite surveys to position offshore structures have been reported in areas of the Canadian coastal waters, North Sea and Gulf of Mexico. The navigation or two-dimensional positioning mode and the more accurate three-dimensional positioning mode are the basic Doppler satellite positioning techniques. The Doppler station accuracy is a function of the orbital data accuracy and the method of data reduction. Provided site conditions are met and equipment operation is normal, the accuracy of Doppler satellite positioning of offshore structures is estimated to be 0.5 to 1.5 meters rms in each coordinate. In order to make use of the accuracy inherent in Doppler positioning, care must be taken in relating the positions to the local datum coordinate system.